2023
DOI: 10.1186/s12939-023-01863-0
|View full text |Cite
|
Sign up to set email alerts
|

Dental health status, dentist visiting, and dental insurance of Asian immigrants in Canada

Abstract: Objective This study examined the dental care utilization and self-preserved dental health of Asian immigrants relative to non-immigrants in Canada. Factors associated with oral health-related disparities between Asian immigrants and other Canadians were further examined. Methods We analyzed 37,935 Canadian residents aged 12 years and older in the Canadian Community Health Survey 2012–2014 microdata file. Factors (e.g., demographics, socioeconomic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 37 publications
1
4
1
Order By: Relevance
“…The findings from this study revealed that Asian immigrant women possessed equivalently good self-perceived health and a significantly lower prevalence of dental symptoms among the three groups. Among numerous risk factors which affected dental health status, marital status and age were two factors that significantly correlated with Asian immigrants' prevalence of dental symptoms [23]. However, the results in this study did not show any such factors correlating with prevalence of dental symptoms in female Asian immigrants of child-bearing age.…”
Section: Discussioncontrasting
confidence: 86%
See 3 more Smart Citations
“…The findings from this study revealed that Asian immigrant women possessed equivalently good self-perceived health and a significantly lower prevalence of dental symptoms among the three groups. Among numerous risk factors which affected dental health status, marital status and age were two factors that significantly correlated with Asian immigrants' prevalence of dental symptoms [23]. However, the results in this study did not show any such factors correlating with prevalence of dental symptoms in female Asian immigrants of child-bearing age.…”
Section: Discussioncontrasting
confidence: 86%
“…Moreover, our earlier investigation showed no significant difference of the dental symptoms' occurrence between the whole Asian immigrants with Canadian-born residents. This study reveals a lower risk of experiencing dental symptoms among Asian female immigrants [23]. The findings from this study revealed that Asian immigrant women possessed equivalently good self-perceived health and a significantly lower prevalence of dental symptoms among the three groups.…”
Section: Discussionsupporting
confidence: 47%
See 2 more Smart Citations
“…However, it was impossible to determine the legitimacy of the treatment because the NHID provided only data on the dental service claimed not oral health status. Secondly, dental visits are guessed to be associated with socioeconomic conditions: the higher the household income or education level, the higher the possibility of dental visits [ 55 60 ]. Socioeconomic inequalities in dental visits start from an early stage of life and accumulate over time, thus inducing undesirable effects, especially in patients of low socioeconomic status [ 61 ].…”
Section: Discussionmentioning
confidence: 99%